A preliminary study of green micro-entrepreneurs in Kelantan, Malaysia. - Mohd Rafi Yaacob (Canadian Center of Science and Education, 2010)
A recycling business or a green business which involves micro entrepreneurs is nothing new in Malaysia. Upon the country independence in 1957, green entrepreneurs used to go from house to house with their bicycles or trishaws to buy used bottles as well as cooking utensils (made from copper, aluminium or irons) and old batteries to resell to bigger used items collectors for profits. But in those days, such an entrepreneurship was the last thing thought by ones who wanted to be entrepreneurs because it was considered as a low status business and least profit as well. However, at present this kind of business is steadily growing and profitable enough. As far the environmental management is concerned this kind of entrepreneurship contributes significantly to sustainability as it reduces usage of raw materials as used materials are recycled to produce new products. Notwithstanding with the contribution of this kind of business, there is a dearth of literature of green business in Malaysia as researchers of small and medium enterprises (SMEs) in the country have concentrated their studies in the areas of finance, micro credit, human resource management, strategic management, marketing as well as leadership. Against this background, a study of green entrepreneurship is paramount. In general, amongst important questions sought in this research were: what push and/or pull factors to be green entrepreneurs? what strategies adopted?, what business routines of green entrepreneurs?, what challenges faced by the entrepreneurs?, and what the prospects of green business? This research capitalized a qualitative study where interviews were conducted with two green micro-entrepreneurs in Kota Bharu, Kelantan. The interviews were conducted at the entrepreneurs’ premises at their conveniences and were audio-recorded. The findings from the interviews provided answers to the above-mentioned research questions and to a little extent filled a void in the field of business and natural environment in the country in particular and in developing country in general.